OPTIMALISASI INTEGRATED DIGITAL MARKETING DALAM STRATEGI PEMASARAN UMKM IMAGO RAW HONEY - Silvia Maylinda; Indah Purnama Sari (JABE (Journal of Applied Business and Economic), 2021)
This study aims to analyze the digital marketing strategy in SMEs Imago Raw Honey. The research method used is descriptive qualitative, with data triangulation. The results showed that the Imago Raw Honey SMEs involved digital roles starting from the process of segmentation, targeting, positioning, marketing mix design, and marketing implementation. SMEs Imago Raw Honey market their products online through an integrated optimization of digital marketing tools. The use of digital media really helps Imago Raw Honey SMEs in carrying out their marketing functions effectively and efficiently.